Development of an E-Handbook Based on Research on the Medicinal Plant Premna serratifolia as The Natural Resources of West Kalimantan for High School Students - Pita Sari; Dini Hadiarti; Dedeh Kurniasih (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop a comprehensive e-handbook, containing research-based information on the medicinal plant Premna serratifolia as the natural resources of West Kalimantan for high school students. This research used a research and development (R&D) method with an ADDIE model and was conducted in three high schools in West Kalimantan. Research instruments include validation instruments and student response questionnaires. The research data were analyzed using quantitative data analysis. Expert validators in content, media, and language assessed the e-Hanbook, resulting in validation percentages of 85.4% for content, 82.6% for media, and 81.5% for language. The practicality of the e-Hanbook was tested through initial and final field trials, achieving percentages of 80.8% and 87.2% respectively. Consequently, the research suggests that the e-Hanbook on Premna serratifolia medicinal plants is highly suitable and practical for high school students.